Pengaruh pijat bayi terhadap kenaikan berat badan bayi umur 4 bulan - Mohammad Shoim; Endy Paryanto Prawirohartono; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: Optimum growth and development reflect the interaction among genetics, environments, attitude factors, and positive stimulations. The positive effect of massage on infant growth has long been recognized, but research on this phenomenon has not much been performed. The growth faltering in children begins at 1-6 months of age in Indonesia.Objective: To identify the effect of massage toward weight gain in infants of 4 months old.Method: The study was quasi-experimental with 2 groups of posttest design. The subjects were infants of 4 months old that were born in two hospitals. Those who were born in one hospital were selected as the control group and the rest were selected as the treatment group. The massage was performed twice a week for four weeks. The data of weight, food intake, illness were collected once a week, whereas the data of mothers’ knowledge and attitude toward breast milk were gathered once during the research period.Results: There was a significant effect of massage on weight gain. The median weight gain of the control group and treatment group were 0.40 kg (Q1=0.35; Q3=0.40) and 0.60 kg (Q1=0.50; Q3=0.70) respectively. The massage also affected the waz (weight for age Z-scores) where the median difference of waz at the beginning and the end of the study of the control group was –0.27 (Q1=-0.34; Q3=-0.23), whereas in the treatment group was -0.03 (Q1=-0.13; Q3=0.09). It meant that control group faced the growth faltering of –0.27 SD waz in a month and treatment group did it for –0.03 SD waz in a month.Conclusion: Infants who got massage treatment had higher weight gain than those who did not.